2016
DOI: 10.1111/asj.12729
|View full text |Cite
|
Sign up to set email alerts
|

Influence of procyanidin supplementation on the immune responses of broilers challenged with lipopolysaccharide

Abstract: In the present study, the effect of dietary procyanidin (PCA, from pine needles) supplementation on the innate immunity of broilers were investigated. The experiment was designed as a 2 × 4 factorial arrangement (eight cages / treatment; six birds (one-day-old) / cage) with dietary PCA concentrations (0, 0.05, 0.075 and 0.1%) and two immune treatments (injection of lipopolysaccharide (LPS) (0.5 mg/kg body weight) or saline). LPS was dissolved in sterile 9 g/L (w/v) NaCl solution at 16, 18, 20 days of age to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
5
14
0
1
Order By: Relevance
“…In our study, the serum levels of IL-1β and TNF-α were significantly increased in chicks challenged with LPS. A similar result was also observed in other studies (Wu, Wang, & Qi, 2017;Zhang et al, 2013). Furthermore, in the current results, we found that berberine can regulate serum IL-1β…”
Section: Itemsupporting
confidence: 93%
“…In our study, the serum levels of IL-1β and TNF-α were significantly increased in chicks challenged with LPS. A similar result was also observed in other studies (Wu, Wang, & Qi, 2017;Zhang et al, 2013). Furthermore, in the current results, we found that berberine can regulate serum IL-1β…”
Section: Itemsupporting
confidence: 93%
“…In total, 16 articles with 887 participants measured hs-CRP (Basu et al, 2011;Bogdanski et al, 2012;de Maat et al, 2000;Dower et al, 2015;Fukino et al, 2005;Fukino et al, 2008;Gutierrez-Salmean et al, 2016;Hu et al, 2016;Hussain et al, 2017;Mielgo-Ayuso et al, 2014;Mombaini & Jafarirad, 2017;Nogueira et al, 2017;Oyama, Maeda, Kouzuma, et al, 2010;Ryu et al, 2006;Shin et al, 2018;Sone et al, 2011), seven articles with 302 participants measured IL-6 (Basu et al, 2011;de Maat et al, 2000;Dower et al, 2015;Mombaini & Jafarirad, 2017;Nogueira et al, 2017;Oyama, Maeda, Sasaki, et al, 2010;Ryu et al, 2006), and six articles with 256 participants measured TNF-α (Bogdanski et al, 2012;de Maat et al, 2000;Dower et al, 2015;Mombaini & Jafarirad, 2017;Nogueira et al, 2017;Oyama, Maeda, Sasaki, et al, 2010). nevertheless, the results were affected by the sex of participants.…”
Section: Discussionmentioning
confidence: 96%
“…Interventions were performed by taking both green tea leaves and green tea extract. Participants in four articles took green tea leaves (Oyama, Maeda, Kouzuma, et al, 2010;Oyama, Maeda, Sasaki, et al, 2010;Ryu et al, 2006;Sone et al, 2011), in two articles, both green tea extract and green tea leaves were taken, which were included as two separate effects (Basu et al, 2011;de Maat et al, 2000), and 11 articles had prescribed green tea extract (Bogdanski et al, 2012;Dower et al, 2015;Fukino et al, 2008;Fukino et al, 2005;Gutierrez-Salmean et al, 2016;Hu et al, 2016;Hussain et al, 2017;Mielgo-Ayuso et al, 2014;Mombaini & Jafarirad, 2017;Nogueira et al, 2017;Sone et al, 2011). Our meta-analysis included 875 participants with age ≥18 years old, and intervention duration ranged between 2 and 48 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory and consumer pressure to reduce antimicrobial usage in production animals has encouraged studies on alternatives to antimicrobials. Most of these alternatives are feed additives that aim to steer towards a healthy gut microbiota, and towards preserving intestinal integrity and thus reducing excessive inflammatory responses [4, 5]. Examples include short and medium chain fatty acids (e.g.…”
Section: Introductionmentioning
confidence: 99%